Design, syntheses, and characterization of new thermoplastic polyureas based on 3,4-ethylenedioxythiophene - Ojha, U. P.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
New thermoplastic polyureas labeled PUn (n = 2, 3, 4, 6, 7, 9, or 10), based on 3,4-ethylenedioxythiophene (EDOT) with flexible aliphatic spacers, were synthesized and characterized for the first time. EDOT was chosen as a replacement for the aromatic phenyl group in conventional thermoplastics based on urea linkages to improve solubility without compromising the thermal properties. As synthesized, all the samples exhibited a semicrystalline nature. The glass-transition and melting temperatures showed a strong dependence on the spacer length. A comparison of the thermal properties of these polyureas with the corresponding phenyl analogues indicated that EDOT was a viable heteroatomic analogue of the phenyl group to be inserted into the main-chain polyureas without hampering their thermal stability. The polyureas with spacer lengths greater than hexamethylene formed transparent gels in N-methylpyrrolidone, 1,1,2,2-tetrachloroethane, and dimethyl sulfoxide. The molecular packing of the polyureas was assigned with wide-angle X-ray diffraction studies. (c) 2005 Wiley Periodicals, Inc.
Keywords: 3; 4-ethylenedioxythiophene; heteroaromatic polymers; Polyurea; polyurea gels; Thermogravimetric analysis (TGA); thermoplastics; WAXS